Biochemical characterisation of human gastric mucin in normal and diseased states - McLeod, Heather Alison (Cape Technikon, 2012)
Thesis (Masters Diploma (Medical Technology) -- Cape Technikon, Cape Town, 1992 === Gastric cancer, a fatal malignancy, is endemic in the Coloured population of the Western Cape region of South Africa. Diagnosis is based mainly on histologic investigation with patients of either sex being mainly between 40-60 years of age. The extent to which genetic and environmental influences play a role in the aetiology of the disease is unknown. This study is an attempt to biochemically characterise gastric mucins or mucus glycoproteins, (the main gel forming components of crude mucus scrapings off the mucosal surface), in carcinoma of the stomach (HCA), as compared to those in ulcer disease (HGU), post mortem specimens (PM) and samples obtained from organ transplant donor stomachs (HD). The aim of this study is the development of a diagnostic marker within mucus secretions for the detection of pre-malignant disease amongst the high risk population of the Western Cape region of South Africa. Mucins were extracted from crude mucus gel scrapings according to a carefully designed technique in which proteolytic inhibitors were used to minimise the possibility of endogenous proteolysis in the laboratory through possible contamination. Two density gradient ultra-centrifugation steps for 48 hours each at 105,000g in caesium chloride, a well established standard isolation procedure for mucins, gave a yield of pure mucins which fractionated at a density of approximately 1.41gjml in all groups. These mucins, from the HO, PH, HGU and HCA groups eluted mainly in the included volume of a Sepharose 2B column as broad, polydisperse peaks, suggesting that they were degraded and comprised mainly lower molecular weight PAS positive material in relation to large polymeric gel forming mucin.